EFFECT OF THE FEEDING OF Coccinella septempunctata L. ON Aphis fabae Scopoli TREATED WITH DIFFERENT CONCENTRATION AND METHODS OF ROYAL JELLY AND HONEYDEW ON ITS SOME BIOLOGICAL CHARACTERS - Nazar AL-Mallah; J. Muhammed (Mesopotamia Journal of Agriculture)
The feeding of the Lady beetle Coccinella septempunctata L. on black bean aphid Aphis fabae Scolopi which was treated directly and indirectly by three concentration (2, 4, 8%) of royal jelly of the bee and honeydew which excreted by the aphid Pterochlorus persicae (Chold.). The results of this study showed that the ladybeetle fed on black bean aphid treated directly with royal jelly of 8% conc. produced a significant effects on the means of larval development period and pupal period which was 2.10, 2.50, 2.50, 3.30 and 3.80 days for 1st, 2nd, 3rd, 4th Instars and pupal stage period respectively, in comparison with 2.90, 2.90, 2.90, 4.00 and 4.30 days respectively for control treatment and showed a significant effects on the means of pre – oviposition period, oviposition period, number of egg per female, incubation period and eggs hatching percentage which reached 4.60, 27.40, 681.40, 2.61 and 94.00% respectively, compared with 6.60, 24.00, 602.40, 3.28, and 80% respectively for the control.